Exploring the potential of immersive journalism in Indonesia - Ananda, Sandy; Hero, Eko; Astini, Bunga (Faculty of Communications Science, Dr. Soetomo University, 2025)
The use of technology in the world of journalism continues to grow rapidly, one form of this innovation being immersive journalism. This study aims to map Indonesia's readiness to develop immersive journalism through the aspects of news reporting, user literacy, as well as ethics and regulations. It uses a qualitative method with a narrative literature review approach to examine the format of immersive journalism in a flexible and exploratory manner, in searching for literature with broad and complex topics. 33 scientific articles and 1 book were selected through a data source evaluation process using inclusion and exclusion criteria based on indexed journals, books, open access, and relevance to the research objectives. In addition, 9 government policy documents were used as grey literature and 3 websites as supporting sources. The findings reveal the advantages of Immersive Journalism in terms of interactivity, presence, emotional engagement, and empathy. Challenges include ethics, implementation, and audience acceptance. Various opportunities emerge from the combination of local potentials such as support from the National Long-Term Development Plan for 2025-2045 policy, production and enhancement of immersive technology education, growth in the virtual reality headset market, and selection of long-term topics. Challenges related to the need for specific ethical regulations for immersive journalism can refer to policies and laws in Indonesia